Structural Insights into Subunits Assembly and the Oxyester Splicing Mechanism of Neq pol Split Intein. Issue 7 (19th July 2018) - Gordo, Verónica; Aparicio, David; Pérez-Luque, Rosa; Benito, Antoni; Vilanova, Maria; Usón, Isabel; Fita, Ignacio; Ribó, Marc
Summary: Split inteins are expressed as two separated subunits (N-intein and C-intein) fused to the corresponding exteins. The specific association of both intein subunits precedes protein splicing, which results in excision of the intein subunits and in ligation, by a peptide bond, of the concomitant exteins. Catalytically active intein precursors are typically too reactive for crystallization or even isolation. Neq pol is the trans -intein of the B-type DNA polymerase I split gene from hyperthermophile Nanoarchaeum equitans . We have determined the crystal structures of both the isolated NeqN and the complex of NeqN and NeqC subunits carrying the wild-type sequences, including the essential catalytic residues Ser1 and Thr+1, in addition to seven and three residues of the N- and C-exteins, respectively. These structures provide detailed information on the unique oxyester chemistry of the splicing mechanism of Neq pol and of the extensive rearrangements that occur in NeqN during the association step. Graphical Abstract: Highlights: NeqN is highly structured and has been solved as a dimer NeqN/NeqC complex formation is dictated by ionic interactions and NeqN reorganization Ser1, His61 (NeqN), Asp13 (NeqC), and Thr+1 (C-extein) are key in the splicing process Abstract : Gordo et al. have determined the crystal structures of both the isolated NeqN subunit and the NeqN/NeqC complex. In these structures, Neq pol subunits carry the intein wild-type sequences, including the essential catalytic residues Ser1 and Thr+1, together with several residues from the N- and C-exteins.